(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2010)
Indian entertainment and media i11d11str.· ,s a Ji1st groll’i11g sector of the Indian eco11,m;y a11d tt 111cl11des the re1·e1111es /mm 1·ario11s media. thm are tcle1·isio11. print. radio, film cnre rrainment. out-of-home advertising, 11111sic 111d11srr:,. animation a11d gaming ind11stry (this is 110 included in E&M sector, earlier it was included i11 the lndian TT a11d Software Re,·enues) and Online Advertising or New Media Advertising. Advertisers today are flooded ith advertising options and considerable thought is put iTllo deciding ll’hich media must be chosen for the purpose of nmning the adverllsing campaign. Since most marketers today, have specified advertising agencies who handle the media buying and campaig11 pla11ning Ju11ction for them, decisions regardi11g the budget a/location onto vario11s media is usually taken b\’ markerers, in tandem with the professionals from their respective advertising agn1cies. It is therefore c rucial for the sales team of a11y medwm( print or electro11ic) to be able to convince the advertfaing agencies that a campaign run on the medium would fetch f’.igh returns on investment for the adver//sed brand. 111 light of this symbiotic rela1io11ship between adverrismg agencies, advertisers a11d various media vehicles, this paper explores the altitude of advertisers as well as advertising agencies towa,ds the efficacy of the new medium- Internet. The paper further tries to understand whether there is a discrepancy in the media preferences of the advertisers and the agencies a11d which media do ac/1 of these groups consider more lucra11ve for _ he purpose of run11ing brand led advertmng campaigns.